Energy balance for a hybrid naval propulsion system - Panaitescu Mariana; Panaitescu Fanel-Viorel; Vasilescu Mihail-Vlad; Daineanu Robert-Alexandru (Journal of Shipping and Trade (JST), 2022)
Introduction: The purpose of this paper is to present an analysis on the energy balance of the hybrid energy system and the mooring scheme for a container ship, as well as the energy balance of the electricity generating systems, from unconventional sources. The methods applied to achieve the main objective consist of analytical calculations and simulations in the ANSYS Fluent program for various positions of the analyzed system, as follows: a) technical characteristics of the container ship; b) elements of the hybrid energy system, which uses unconventional energy; c) energy balance of electricity generating systems from unconventional sources; d) connecting conventional and unconventional power sources to the ship's main power bar. Results: Finally of researches, the results obtained are: a) the volume, mass and ascending force of the FLETTNER balloon with helium, assimilated with an airship; b) positioning scheme of large vertical wind turbines installed in the bow of the container ship and in the stern of the container ship; c) the energy balance of electricity generating systems from unconventional sources; d) schemes for connecting conventional and unconventional energy sources to the ship. Conclusions: The calculation of the energy balance of the two types of wind energy capture systems depending on the speed of the ship, in ideal wind conditions and depending on the number of vertical wind turbines running, which use wind energy. Of course, it will never be necessary to turn on all wind power equipment at full capacity. The FLETTNER balloon can generate more power and for this reason, we must to present the number and diameter of cables needed to transmit electricity. Through this research, following the installation of the elements of the hybrid diesel-electric power system with energy from conventional (fossil fuels) and unconventional energy sources (a FLETTNER balloon with helium and four large vertical wind turbines) placed on a ship container portability, both the manoeuvrability and the stability of the ship, do not change fundamentally.
Keywords: 650; Energy; FLETTNER balloon; Hybrid; Ship; Turbine; Wind